The Language Connection: How Your Native Tongue Affects Foreign Language Acquisition - G’ulomova Odina G’ofurjon qizi, (NAZARIY VA AMALIY FANLARDAGI USTUVOR ISLOHOTLAR VA ZAMONAVIY TA'LIMNING INNOVATSION YO'NALISHLARI, 2024)
This paper explores the dynamic relationship between native language (L1) and foreign language (L2) acquisition. It examines how L1 can serve as both an advantageous foundation and a source of interference in the language learning process. Through various examples, the study highlights the cognitive benefits of bilingualism, the significance of linguistic similarities, and the cultural implications of maintaining a connection to one’s native language. By understanding this interplay, learners can enhance their foreign language journey, transforming challenges into opportunities for growth.